1996
DOI: 10.1108/02621719610146211
|View full text |Cite
|
Sign up to set email alerts
|

Strategic management and the case method

Abstract: Reports the results of a survey of UK lecturers involved in teaching strategic management to postgraduate and post‐experience students. Identifies the lecturer’s objectives in using case studies and evaluates the effectiveness of the case method in achieving those objectives. Finds that the method is successful in achieving participation and in developing communication and interpersonal skills, but less successful in the development of strategic analysis. Finds that a wide range of other methods are used in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
18

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 10 publications
2
43
0
18
Order By: Relevance
“…Specifically, officers indicated that the module made them think about the Tripwire scenario in a way different from a way in which they would usually approach the scenario. Because one objective of case method instruction is to encourage students to broaden their thinking and challenge their perspectives (Crittenden, Crittenden, & Hawes, 1999;Jennings, 1996;Kreber, 2001;Richardson, 1994;Stewart & Dougherty, 1993), these findings are encouraging.…”
Section: Research On Axlnetmentioning
confidence: 59%
See 2 more Smart Citations
“…Specifically, officers indicated that the module made them think about the Tripwire scenario in a way different from a way in which they would usually approach the scenario. Because one objective of case method instruction is to encourage students to broaden their thinking and challenge their perspectives (Crittenden, Crittenden, & Hawes, 1999;Jennings, 1996;Kreber, 2001;Richardson, 1994;Stewart & Dougherty, 1993), these findings are encouraging.…”
Section: Research On Axlnetmentioning
confidence: 59%
“…In actuality, case method instruction has been a popular approach for developing leaders since the early twentieth century when Harvard made case method instruction an integral part of its Business School curriculum (Gragg, 1982;Jennings 1996). Since that time, case method instruction can be found in many professional disciplines, including the medical, teaching, and legal domains (e.g., Jennings, 1996;Stewart & Dougherty, 1993;Tarnvik, 2002;Wright, 1999). While many variations of case method instruction exist today, case method instruction generally consists of two fundamental components.…”
Section: Leader Development With Stories and Case-methods Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Each role highlights a different approach for moving students through the learning process. Jennings (1996Jennings ( , 1997 and Siciliano and McAleer (1997) extend this work by offering insights to the specific use of the case method in the teaching of strategic management which is the primary focus of this research.…”
Section: Traditional Case Methodsmentioning
confidence: 82%
“…In short, cases pose exactly the sort of situations students are likely to encounter in their managerial roles (Orpen 2000). Jennings (1996) summarises some frequently cited learning objectives associated with the case study method. Cases can be used to acquire knowledge, confront the complexity of specific situations, develop analysis and synthesis and relate theory to practice.…”
Section: T Th He E C Ca As Se E S St Tu Ud Dy Y M Me Et Th Ho Od Dmentioning
confidence: 99%